2020
DOI: 10.1007/s11239-020-02318-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated coagulopathy in critically ill patients: A hypercoagulable state demonstrated by parameters of haemostasis and clot waveform analysis

Abstract: Patients with COVID-19 are known to be at risk of developing both venous, arterial and microvascular thrombosis, due to an excessive immuno-thrombogenic response to the SARS-CoV-2 infection. Overlapping syndromes of COVID-19 associated coagulopathy with consumptive coagulopathy and microangiopathy can be seen in critically ill patients as well. Blood was collected from 12 Intensive Care Unit (ICU) patients with severe COVID-19 who were on either mechanical ventilation or on high flow oxygen with a PaO2/FiO2 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 39 publications
(41 reference statements)
5
41
0
Order By: Relevance
“…The pathophysiology of all ARDS includes microthrombi and macrothrombi formation in the pulmonary vasculature ( 34 ). Similarly, COVID-19 critical illness is associated with a hypercoagulable state and clinical and histopathologic data have confirmed microthromboembolic disease and associated decreases in pulmonary perfusion in patients with COVID-19 ( 23 , 25 , 26 , 35 , 36 ). The degree of microthrombi in COVID-19 specimens is greater than patients with ARDS from other etiologies, but the clinical implications are unclear ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 87%
“…The pathophysiology of all ARDS includes microthrombi and macrothrombi formation in the pulmonary vasculature ( 34 ). Similarly, COVID-19 critical illness is associated with a hypercoagulable state and clinical and histopathologic data have confirmed microthromboembolic disease and associated decreases in pulmonary perfusion in patients with COVID-19 ( 23 , 25 , 26 , 35 , 36 ). The degree of microthrombi in COVID-19 specimens is greater than patients with ARDS from other etiologies, but the clinical implications are unclear ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 87%
“…As a result, 17 studies [1026] with a total of 1187 patients were subjected to qualitative analysis and meta-analysis (Figure 1 and Table 1). Quality assessment with NOS showed that 13 studies [10,13– 19,21–24,26] were of good quality with ≥ 7 NOS score and four studies [11,12,20,25] were considered as moderate quality with six NOS score (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…4 ) and that fibrinogen theoretically enhances the speed and acceleration of clot formation, high fibrinogen levels could explain these modulations in COVID-19 subjects. Fan, B.E.,et al demonstrated that Factor VIII levels and VWF levels increased together with the raised APTT clot waveform parameters and fibrinogen 27 . As shown in Supplementary Figure S1 , we observed the existence of abnormal clot waveform in the subjects with hemophilia, suggesting the possible involvement of Factor IX as well as Factor VIII in the abnormal clot waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, HCoV-229E, another type of coronavirus, reportedly disturbs phospholipid homeostasis in infected cells 32 . Regarding the clot waveform analyses and COVID-19, recent reports have demonstrated that the first-derivative and second-derivative peak levels were higher, and the minimum second-derivative peak level were lower or tended to be lower in critically ill COVID-19 subjects 27 , 33 , 34 . Although in the present study, we observed no difference in the APTT clot waveform parameters among mild, moderate, and severe COVID-19 subjects (Supplemental Figure S5 ), the modulation of these parameters in the COVID-19 subjects would be concordant with the previous studies, considering the time course of these parameters (Fig.…”
Section: Discussionmentioning
confidence: 99%